2019
DOI: 10.3390/antibiotics8020068
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antibiotic Resistance (MAR), Plasmid Profiles, and DNA Polymorphisms among Vibrio vulnificus Isolates

Abstract: Sixty strains (n = 60) of Vibrio vulnificus were examined for their multiple antibiotic resistance (MAR) index, plasmid profiles, and DNA polymorphisms. Thirty-seven strains (n = 37) were isolated from cockles (Anadara granosa) in Malaysia, while 23 (n = 23) isolates were isolated from clams (Mercenaria mercenaria) in Qatar. All isolates were resistant to two or more of the antibiotics tested, with the most common resistances were demonstrated towards penicillin (93%), ampicillin (70%), cephalothin (65%), clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…In the present study, 10-years' worth of microbiological and resistance data for Gram-negative UTIs in Hungary were assessed, in light of existing and novel resistance classifications [24,28,30]. The surveillance of the etiology and susceptibility patterns in UTIs allow for targeted stewardship interventions in various healthcare facilities [37,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, 10-years' worth of microbiological and resistance data for Gram-negative UTIs in Hungary were assessed, in light of existing and novel resistance classifications [24,28,30]. The surveillance of the etiology and susceptibility patterns in UTIs allow for targeted stewardship interventions in various healthcare facilities [37,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…As a part of this study, a predictive composite score was also introduced (pMAR), which is an augmented version of the multiple antibiotic resistance (MAR) index described previously [28,29], based on the formula (1) below, where n MDR is the number of MDR isolates in the respective category (e.g., E. coli, Citrobacter-Enterobacter-Serratia), AB MDR is the minimum number of antibiotics needed for the respective bacterial group to become MDR, n all is the number of all isolates in the respective group and AB all is the number of all antibiotics tested. The pMAR value corresponds to the percentage chance (0%-100%) that the isolated pathogen in the present clinical situation will not be treatable by first-line antibiotics, based on local epidemiological characteristics.…”
Section: Classification Of Isolates Into Resistance Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh, Ahmmed et al (2019) found tlh, pirA and pirB genes from two AHPND positive V. parahaemolyticus strains isolated from shrimp (Penaeus monodon) (15) . The previous studies in Malaysia showed that the most virulent of the non-cholera vibrios (V. vulnificus) have various virulence factors that facilitate the development of clinical disease (16) . V. vulnificus also have been implicated in fish diseases such as septicemia (3) .…”
Section: Isolation Of Pathogenic Vibriomentioning
confidence: 99%
“…V. vulnificus strains are generally susceptible to most veterinary and clinically used antibiotics [ 2 , 25 ]. However, a large proportion of resistance has been observed in various environmental niches, which are categorized into three levels: a low resistance against cefepime, kanamycin, oxytetracycline, tetracycline, nalidixic acid, and oxalinic acid; an intermediate resistance against aztreonam, streptomycin, erythromycin, vancomycin, clindamycin, ampicillin, penicillin, and gentamycin; and a complete resistance against tobramycin and cefazolin [ 26 , 27 , 28 ]. Such an increasing rate of antibiotic resistance in various environmental niches is correlated to the extensive use of antibiotics in agriculture, aquaculture, and clinical settings.…”
Section: Introductionmentioning
confidence: 99%